A comprehensive comparison of two variable importance analysis techniques in high dimensions: Application to an environmental multi-indicators system. (August 2015) - Wei, Pengfei; Lu, Zhenzhou; Song, Jingwen
Abstract: Permutation variable importance measure (PVIM) based on random forest and Morris' screening design are two effective techniques for measuring the variable importance in high dimensions. The former technique is developed in the machine learning discipline and widely used in bioinformatics, while the latter technique is popular in scientific computing. We present three main contributions to variable importance analysis (VIA). First, through theoretical derivation, we show that the PVIM converges to double the non-standardized Sobol' total effect index. This observation indicates that the PVIM is especially useful for variable screening as it captures both the individual and interaction effects. Second, three numerical examples with different types of model behavior are presented for comparing the performances of these two techniques. The main conclusions are as follows. For high-dimensional additive or approximately additive models, the PVIM is much more efficient than Morris' screening design when used for both variable importance ranking and variable screening. For high-dimensional models mainly governed by interaction effects, the performance of PVIM degrades, but it is still a competitive technique. Finally, the two techniques are applied to an environmental multi-indicators system for improving the robustness of the partial order structure of this system. Highlights: The relative merits of PVIM and Morris' design are compared. The PVIM is proved to converge to double the unscaled Sobol' total effect indices. The two techniques are compared with three high-dimensional examples. The two techniques are applied to an environmental multi-indicators system.